GWAS for male-pattern baldness identifies 71 susceptibility loci explaining 38% of the risk - Pirastu, Nicola; Joshi, Peter K.; de Vries, Paul S.; Cornelis, Marilyn C.; McKeigue, Paul M.; Keum, NaNa; Franceschini, Nora; Colombo, Marco; Giovannucci, Edward L.; Spiliopoulou, Athina; Franke, Lude; North, Kari E.; et al. (Nature communications, 2017)
Male pattern baldness (MPB) or androgenetic alopecia is one of the most common conditions affecting men, reaching a prevalence of ~50% by the age of 50; however, the known genes explain little of the heritability. Here, we present the results of a genome-wide association study including more than 70,000 men, identifying 71 independently replicated loci, of which 30 are novel. These loci explain 38% of the risk, suggesting that MPB is less genetically complex than other complex traits. We show that many of these loci contain genes that are relevant to the pathology and highlight pathways and functions underlying baldness. Finally, despite only showing genome-wide genetic correlation with height, pathway-specific genetic correlations are significant for traits including lifespan and cancer. Our study not only greatly increases the number of MPB loci, illuminating the genetic architecture, but also provides a new approach to disentangling the shared biological pathways underlying complex diseases. Male pattern baldness (MBP) is a complex trait that has genetic associations. Here, Pirastu and colleagues perform a genome-wide association study to show 71 susceptibility loci associated with MBP — 30 of which are novel — and that these loci can explain 38% of heritability.